Proceedings against the government by members of the armed forces : a comparison in practice between the United Kingdom, United States of America and Malaysia - Daud, Mahyuddin (LexisNexis, 2011)
It has been accepted for many centuries that the Crown or the government in its personal capacity is immune from any wrongs, be it criminal or civil proceedings.1 This aspect of the Constitution found expression in such ancient legal maxims and principles as 'the King can do no wrong' and 'the King cannot be sued in his own courts'. However, as time goes by, the above doctrines seems cannot be sustained for long as more and more cases involving the government comes before the court of law. Furthermore, some countries, to a certain extent, have forfeited the protective veils that grant immunity towards the government. Consequently, the government has to be answerable for its conducts in the administration of the country. In light of the above, this paper intends to study the governmental liability relating to injury or death of military personnel.